From Therapy to Instruction: The Effect of Systemic Strategies on the Oral Performance of Foreign Language Learners - Ana Clara Sánchez Solarte; Andrés Sánchez Solarte (Asociación Colombiana de Profesores de Ingles, 2017)
This paper reports the results of a group intervention based on strategies derived from the systemic therapy model-brief strategic therapy. These strategies aimed at decreasing the anxiety levels commonly found in oral performance tasks related to L2 learning. Thirteen students from different semesters who belonged to two foreign language teaching programs participated in four weekly 40-minute group sessions. The pre- and post-assessments suggest a meaningful reduction of anxiety levels (t = 8.978 p < 0.05; ES = 2.49). The results suggest that the application of the strategies is highly effective and beneficial for anxious L2 learners.